Spinal cord injury under sacral nerve magnetic stimulation: Changes in serum oxidative stress factors, inflammatory factors and coagulation function - Wu, Ruimin; Li, Jin (Journal of Medical Biochemistry, 2025)
Objective: This study observed the effect of sacral nerve magnetic stimulation (SNM) on neurogenic bladder (NB) after spinal cord injury (SCI). Pay close attention to the changes in serum oxidative stress factors, inflammatory factors and coagulation function.Methods: A total of 134 SCI-induced NB patients admitted between February 2021 and January 2025 were enrolled. All participants received information-motivation-behavioral skills (IMB) management and were randomized into two groups: a conventional group (n = 71) receiving conventional treatment and an SNM group (n = 63) treated with SNM. Laboratory analyses included coagulation markers (D-dimer, fibrinogen), oxidative stress indicators (superoxide dismutase [SOD], glutathione peroxidase [GSH-Px], malondialdehyde [MDA]), and inflammatory mediators (IL-1β, IL-6, TNF-α, hs-CRP).Results: Coagulation function also improved, with significantly lower D-dimer and fibrinogen levels in the SNM group (P < 0.05). Regarding oxidative stress, the SNM group exhibited higher SOD and GSH-Px activity alongside reduced MDA levels (P < 0.05). Furthermore, inflammatory markers (IL-6, TNF-α) were significantly lower in the SNM group (P < 0.05).Conclusion: SNM can alleviate the stress response and inflammatory response of patients with SCI-induced NB, relieve the hypercoagulable state of blood, and has certain clinical application value.